A Comparison of the Fibrinolytic and Fibrinogenolytic Effects of Plasminogen Activators and Proteolytic Enzymes in Plasma - Sawyer, William D.; Alkjaersig, Norma; Fletcher, Anthony P.; Sherry, Sol (Thrombosis and Haemostasis, 1961)
1. A sensitive test system has been described whereby the respective fibrinolytic and fibrinogenolytic effects of plasminogen activators and proteolytic enzymes in plasma may be quantitated separately by use of isotopically labeled substrates.2. Plasminogen activators in the plasma-clot system were demonstrated to lyse more fibrin per unit fibrinogen lysed than either plasmin or trypsin. No evidence was obtained to suggest the formation of a plasmin-antiplasmin complex with special “fibrinolytic” porperties.3. Comparison of the effects of streptokinase and urokinase in plasma revealed discrete differences in the ratio of their fibrinolytic-fibrinogenolytic activities.